2008
DOI: 10.1111/j.1749-7345.2008.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Ginseng Herb (Ginsana® G115) Supplementation on Growth, Feed Utilization, and Hematological Indices of Nile Tilapia, Oreochromis niloticus (L.), Fingerlings

Abstract: The present study was conducted to evaluate the effect of dietary ginseng herb (Ginsana® G115) supplementation on growth performance, feed utilization, and hematological indices of Nile tilapia, Oreochromis niloticus (L.), fingerlings. A total of 378 Nile tilapia fingerlings with an average body weight of 24.4 ± 0.2 g were divided in the six experimental treatments (three replicates each). The experiment was conducted for 17 wk. Six isonitrogenous, 27.2% digestible protein and isocaloric, 12.3 MJ/kg digestible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
75
4
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 31 publications
22
75
4
7
Order By: Relevance
“…It has been reported that dietary supplementation with thyme (Thymus vulgaris) and vitamin E resulted in an improvement in growth performance and fed efficiency of juvenile Acipenser stellatus (Goda 2008). Dorojan et al (2015) also reported that fish fed diets containing at least 200 mg kg -1 of ginseng herb (Ginsana® G115) for 17 weeks, had enhanced growth performance, feed efficiency, and hematological indices.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that dietary supplementation with thyme (Thymus vulgaris) and vitamin E resulted in an improvement in growth performance and fed efficiency of juvenile Acipenser stellatus (Goda 2008). Dorojan et al (2015) also reported that fish fed diets containing at least 200 mg kg -1 of ginseng herb (Ginsana® G115) for 17 weeks, had enhanced growth performance, feed efficiency, and hematological indices.…”
Section: Discussionmentioning
confidence: 96%
“…Farklı balık türlerinde bitkilerle yapılan besleme çalışmalarında, protein etkinlik oranı (PER), ve prodüktif protein değerinde (PPV) artış olması bu hipotezi desteklemektedir (Shalaby vd., 2006;Goda, 2008;Nya ve Austin 2009). Bitkisel ürünlerin gökkuşağı alabalıklarında büyüme üzerine etkisi ile ilgili çalışmalar mevcut olup, Erol-Florian vd.…”
Section: Tartişma Ve Sonuçunclassified
“…Ülkemizde ise gerek bakteriyel dirence yol açabileceği gerekse hayvansal yan ürünlerde kalıntı bırakarak insan sağlı-ğını tehdit edebileceği endişesiyle antibiyotiklerin yem katkı maddesi olarak kullanımı eş zamanlı olarak yasaklanmıştır. Bu yasaklanma ile birlikte gerek gastro-intestinal mikrofloranın sağlığını koruyarak bakteriyel hastalıkların kontrol altına alınması gerekse hayvanların bağışıklık sisteminin güçlendirilmesi ve büyüme performansının desteklenmesi, mortalitenin azaltılması amacıyla antibiyotiklere alternatif olabilecek bazı tıbbi bitki türlerinin yem katkı maddesi olarak kullanılmasının iyi bir alternatif olduğu bildirilmektedir (Hermann vd., 2003;Goda, 2008;Keser ve Bilal, 2008).…”
Section: Introductionunclassified